Estratégias argumentativas na produção escrita de artigo de opinião no ensino fundamental - Ferreira, Mayara de Souza (2018)
The argumentation is present in several daily social practices, from informal situations to formal contexts, such as essentially argumentative texts, external evaluations and professional situations. At such moments, the student needs a discursive competence about the argumentation, its methods and processes in order to make it effective (BRETON, 2003). Thus, this study purpose to contribute to the teaching and learning of the written production of the genre of opinion by students of the 9th grade of Elementary School of a state public school in Fortaleza-CE. In order to do so, we analyze the construction of the argumentation in the production of texts of the opinion article genre, trying to investigate the argumentative strategies that students use in the writing of argumentative texts. The proposal consisted in elaborating a sequence of teaching strategies, based on the difficulties identified in the initial production of the students, for integration between the scope of the argumentative sequence and of the pragmatic argumentation to the teaching of the textual genre article of opinion from the textual-interactive perspective. The methodology adopted is based on action research, according to Thiollent (2008). As presuppositions of the Linguistic of the Text, it adopts the sociointerational conception of the language, defended by Koch (1992); the teaching of writing as a process, following the contributions of Serafini (1994), Geraldi (1999), Antunes (2003) and Vieira (2005); the study of textual genres in the classroom is according to Antunes (2003), Dolz, Noverraz and Schneuwly (2004), Marcuschi (2010) and Koch and Elias (2014). Furthermore, we follow Adam's (1992) contributions in the textual organization of the argumentative sequence and the assumptions of argumentation from the perspective of the New Rhetoric based on Perelman and Tyteca (2002) revisited by Fiorin (2015). The didactic procedure used is the didactic sequence, as directed by Dolz, Noverraz and Schnewly (2004), for the development of the production of the genre opinion article. The analysis of the results allows to identify evolutions in the productions developed at the end of the didactic sequence, thus proving its effectiveness for the teaching of the textual genre opinion article. The aim is to demonstrate, through the obtained results, that, through argumentative strategies, it is possible to reach a productive language teaching of the genre of opinion.